2023
DOI: 10.3390/admsci13120251
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Turnover Intentions in Employees of the Portuguese Tax and Customs Authority: Mediating Effect of Burnout and Moderating Effect of Motivation

Mariana Freitas,
Ana Moreira,
Fernando Ramos

Abstract: The main objective of this study was to study the effect of occupational stress on turnover intentions, as well as determine whether this relationship is mediated by burnout levels and moderated by motivation. The sample size of this study consisted of 603 participants, all employees of the Portuguese Tax and Customs Authority, which is part of the Ministry of Finance and belongs to the Direct State Administration. The results indicate that occupational stress (with managers, career and pay, and overwork) has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In contrast to the paucity of literature connecting ICC to job burnout, a large body of literature exists that explores the relationship between job stress and burnout across a variety of work-related contexts (e.g., Innstrand et al, 2004 ; Leung et al, 2011 ; Silbiger and Pines, 2014 ; Mullen et al, 2018 ; Freitas et al, 2023 ). Stress can be defined as “a nonspecific response of the body to any demand” ( Seyle, 1983 , p. 127).…”
Section: Literature Review Theory and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the paucity of literature connecting ICC to job burnout, a large body of literature exists that explores the relationship between job stress and burnout across a variety of work-related contexts (e.g., Innstrand et al, 2004 ; Leung et al, 2011 ; Silbiger and Pines, 2014 ; Mullen et al, 2018 ; Freitas et al, 2023 ). Stress can be defined as “a nonspecific response of the body to any demand” ( Seyle, 1983 , p. 127).…”
Section: Literature Review Theory and Conceptual Frameworkmentioning
confidence: 99%
“…For professional aspect, job satisfaction ( Dartey-Baah et al, 2020 ), organizational commitment ( Wong et al, 2021 ), and job burnout are common symptoms due to job stress. Abundant research has found that job stress is the antecedent of burnout ( Nyssen et al, 2003 ; Leung et al, 2010 ; Li et al, 2015 ; Luo et al, 2016 ; Mnif and Rebai, 2022 ; Freitas et al, 2023 ).…”
Section: Literature Review Theory and Conceptual Frameworkmentioning
confidence: 99%
“…In recent decades, the technological revolution has brought about a significant change in the labour market, speeding up the pace of work and increasing the overload of information. The characteristics of the contemporary labour market, i.e., temporary contracts, psychological contracts between workers and employers, and new perceptions of employability, call into question job security, thus representing an inexhaustible source of professional stress, which is defined by the worker's inability to deal with the sources of stress, and in chronic cases, burnout, which can lead to mental and physical exhaustion requiring complex medical assistance [1][2][3].…”
mentioning
confidence: 99%